2021
DOI: 10.1021/acs.nanolett.1c00832
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid DNA Nanoparticles for Nonviral Oral Gene Therapy

Abstract: Herein, a bile acid-inspired triple padlock oral gene delivery platform is developed, facilitating the protection of the therapeutic gene from gastrointestinal degradation, selective intestinal accumulation through a bile acid-specific transporter, and transportation of pDNA NPs through the enterohepatic recycling system. This nonviral oral gene delivery nanoparticle exhibits excellent gene expression kinetics in in vitro, in vivo, and ex vivo studies. A single oral dose leads to maintaining normoglycemia for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The in vivo toxicity study of GENE/PTCA has been evaluated after long-term treatment, with the highest dose in Lepr OB /Lepr OB mice after repeated oral administration for 20 weeks. We previously assessed the safety of this system in Lepr DB /Lepr DB mice in a prior study . We did not observe any organ damage or enlargement after long-term treatment, indicating that oral gene therapy with GENE/PTCA did not induce acute toxicity in obese mice (Figure S10).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The in vivo toxicity study of GENE/PTCA has been evaluated after long-term treatment, with the highest dose in Lepr OB /Lepr OB mice after repeated oral administration for 20 weeks. We previously assessed the safety of this system in Lepr DB /Lepr DB mice in a prior study . We did not observe any organ damage or enlargement after long-term treatment, indicating that oral gene therapy with GENE/PTCA did not induce acute toxicity in obese mice (Figure S10).…”
Section: Resultsmentioning
confidence: 80%
“…The apical sodium bile acid transporter (ASBT) is an active transporter found in the ileum of the small intestine that transports hepatic bile salts (BSs). , Our original research on ASBT-mediated drug delivery systems showed that they could transport a high percentage of BSs that reach the ileum . Inspired by this, we hypothesized that modifying the surface of an oral nanoformulation containing a plasmid encoding the GLP-1 gene could mimic bile acid physiology . We previously reported proof-of-principle studies on this oral GLP-1 gene formulation and have now demonstrated its ability to treat diabetes and morbid obesity with a minimal therapeutic dose .…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples was collected at 31-day postinjection to determine whether the hydrogel-based drug delivery system could cause blood toxicity in vivo . The CBC profile was analyzed using an automated hematology analyzer according to previously reported protocol …”
Section: Methodsmentioning
confidence: 99%
“…The CBC profile was analyzed using an automated hematology analyzer according to previously reported protocol. 65 Histopathological Analysis. The heart, kidney, liver, lung, spleen, and gastrocnemius of the experimental rats were harvested to analyze tissue histopathology at predetermined time points (three rats per time point): 7-and 31-day postinjection.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The inherent nature of NAs such as large molecular weight and negative charge combined with physiological aspects like extreme pH in GIT, enzymatic degradation, mucosal layer barrier and peristalsis pose additional challenges for their successful oral delivery [ 90 ]. Therefore, oral delivery of NA requires extra caution to protect its structural integrity along with its chemical stability from various factors responsible for degradation [ 91 ]. Despite of all these obstacles, several researchers have formulated delivery systems to overcome these challenges and have shown successful oral gene delivery in vivo in mice and swine [ 1 , 34 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%